2008
DOI: 10.1681/asn.2007121304
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Induces the Inflammatory Molecule ICAM-1 in Endothelial Cells

Abstract: Epidemiologic studies have linked fructose intake with the metabolic syndrome, and it was recently reported that fructose induces an inflammatory response in the rat kidney. Here, we examined whether fructose directly stimulates endothelial inflammatory processes by upregulating the inflammatory molecule intercellular adhesion molecule-1 (ICAM-1). When human aortic endothelial cells were stimulated with physiologic concentrations of fructose, ICAM-1 mRNA and protein expression increased in a time-and dosage-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 31 publications
(33 reference statements)
5
121
0
4
Order By: Relevance
“…18,24 Fructose can also increase the expression of intercellular adhesion molecule-1 in vascular endothelial cells throughout the kidney. 25 In addition, selective injury to the proximal tubule can result in glomerular damage, possibly because of connecting tubule glomerular feedback in which reflex arteriolar vasodilation from tubular damage causes increases in glomerular pressure. 26,27 Interestingly, repeated proximal tubular damage has been proposed as a pathogenic mechanism in the progression of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…18,24 Fructose can also increase the expression of intercellular adhesion molecule-1 in vascular endothelial cells throughout the kidney. 25 In addition, selective injury to the proximal tubule can result in glomerular damage, possibly because of connecting tubule glomerular feedback in which reflex arteriolar vasodilation from tubular damage causes increases in glomerular pressure. 26,27 Interestingly, repeated proximal tubular damage has been proposed as a pathogenic mechanism in the progression of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional studies have reported an association between SSB consumption and incident hypertension: Nguyen et al found a relation between intake of sodas sweetened with HFCS and hypertension in a population of adolescents, 5 and an analysis of NHANES data found an increased prevalence of hypertension among individuals consuming higher than average amounts of fructose (≥ 74 g/d) derived mostly from SSBs. 6 Because SSBs contain fructose, which in animal studies has been shown to cause renal damage, increased gastrointestinal sodium uptake, and endothelial dysfunction, [17][18][19] it was hypothesized that the HFCS in sugary beverages was responsible for the increased risk of incident hypertension. In a prospective study, however, Forman et al found no association between total fructose intake (regardless of source) and hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular dysfunction due to fructose-rich diet has been reported in rats. In addition, impaired endothelium-dependent relaxation has been found to occur after fructose intake in mice (Delbosc et al, 2005;Glushakova et al, 2008). There is now evidence that insulin modulates the expression of endothelial nitric oxide synthase (eNOS) and stimulates nitric oxide (NO) production, causing vasodilation.…”
Section: Introductionmentioning
confidence: 99%